Upward Pricing Pressure in Two‐sided Markets. (21st August 2013) - Affeldt, Pauline; Filistrucchi, Lapo; Klein, Tobias J.
<x xml:space="preserve">Abstract</x> Measuring upward pricing pressure (UPP) has recently been proposed by Farrell and Shapiro (2010) as an alternative screening device for horizontal mergers. We extend the concept of UPP to two‐sided markets. Examples of such markets are the newspaper market, where the demand for advertising is related to the number of readers and the market for online search, where advertising demand depends on the number of users. The formulae we derive depend on four sets of diversion ratios that can either be estimated using market‐level demand data or elicited in surveys. In an application, we show that it is important to take the two‐sidedness of the market into account when evaluating UPP.